Prevalence of prehypertension, hypertension, stress, anxiety among undergraduate medical students, and its association with cognitive failure: A cross-sectional study - Vineeta Chadha; Swarna Rastogi; Sampa Choudhury; Madhu Chaudhary; Harvir Singh Sodhi; Qazi Rais Ahmad (Asian Journal of Medical Sciences, 2023)
Background: Research shows that both hypertension and prehypertension accelerate the decline in standardized global cognitive performance. Two important risk factors for development of elevated BP are stress and anxiety. Hence, the study also focuses on assessing stress and anxiety in undergraduate medical students using validated questionnaires.